Analysis of the Effect of Motivation and Training on the Performance of Nurses in Datu Beru Takengon Public Hospital - Vina Rezeki; Arifah Devi Fitriani; Iman Muhammad; Lucia Lastiur (Newinera Publisher, 2020)
Nurses who work in emergency room must have more skills, which is implied for every nurse who works in the emergency room to have a good performance. The study aims to analyze the influence of motivation and training on the performance of nurses in the emergency room at Datu Beru Takengon General Hospital in 2018.The design used a quantitative analytic survey. The population were all nurses in the emergency room of Datu Beru Hospital in Takengon by totalling 32 nurses and all were taken as the sample by using total population technique. Data analysis was performed by univariate, bivariate and multivariate analyses.The results showed that out of 15 respondents who had less motivation had a poor performance in the category of less than 9 people (60%) and of the 17 respondents who were motivated, motivation with nurse performance with Chi-Square statistical test obtained p-value =.032 <α .05, which means that there is an influence between training and nurse performance .001 <α .05, which means there is an influence between training and nurse performance.The conclusion is that there is an influence between motivation and training on the performance of nurses in the emergency room. It is recommended that the hospital management pay attention to the performance of the nurses, by giving riward to nurses who have good performance and giving sanctions to nurses who break the rules.